Examine The Capabilities of Biosynthetic Silver Nanoparticles as an Agent Against A549 Lung Cancer Cells - Malaghi, Safaa Karim; Bashra Ali Ghyadh (Indonesian Journal on Health Science and Medicine, 2025)
Targeting cancer cells using nanoparticles is a good way to get around the drawbacks of conventional radiation and chemotherapy. Certain characteristics of nanoparticles, especially silver nanoparticles (AgNPs), include their anticancer efficacy and selective toxicity. Using probiotic bacteria like Lactobacillus plantarum to produce them is an economical and ecologically beneficial approach in the field of nanomedicine. This study's objectives are to create silver nanoparticles (AgNPs) from Lactobacillus plantarum cell filtrate, evaluate their biochemical and physicochemical characteristics, and look into how detrimental they are to lung cancer cells (A549) as opposed to healthy cells (WRL-68). The particles were generated by combining cell filtrate and a silver nitrate solution. The color changed to light brown due to surface plasmon photoreduction (SPR), indicating the creation of nanoparticles. UV-Vis spectroscopy confirmed the formation, revealing an absorption peak at 260 nm. FESEM studies revealed that the nanoparticles were spherical in form, with a diameter of around 31.08 nm. FTIR analysis revealed the presence of functional groups such as hydroxyl (-OH), alkanes (C-H), carbonyl (C=O), and amide (N-H), which help to reduce and stabilize the particles. The MTT test demonstrated that the silver nanoparticles had concentration-dependent toxicity on malignant A549 cells but limited effect on normal WRL-68 cells, indicating potential selectivity. The findings indicate that silver nanoparticles produced by Lactobacillus plantarum are a promising and generally safe approach for anticancer therapeutic applications, emphasizing the need for further research into their molecular mechanisms of action. Highlights: Silver nanoparticles biosynthesized using Lactobacillus plantarum showed spherical shape (31.08 nm) with functional groups aiding stability. AgNPs exhibited concentration-dependent cytotoxicity against A549 lung cancer cells with IC₅₀ = 81.69 µg/mL. Minimal toxicity was observed on normal WRL-68 cells, confirming selective anticancer potential.